Genetic and non-genetic factors affecting calf survivability in Gir crossbreds - MOTE, MAHENDRA GORAKH (Indian Journal of Dairy Science, 2023)
Data on survivability traits of Gir crossbred calves, maintained at RCDP on Cattle, Mahatma Phule Krishi Vidyapeeth, Rahuri, Maharashtra was collected for a period of 15 years (2005-2019) to study effect of genetic and non-genetic factors on survivability traits of calf. Traits studied were survivability at day 0-3, 4-15, 16-30, 3-90, 91-180 and 181-365 days. To determine the effects of genetic and non-genetic factors on survivability traits, least squares analysis of variance (Harvey, 1990) was applied, considering the fixed effects like genetic group, season and period of birth, parity of dam and birth weight of calves. The least square means of survivability per cent of Gir crossbred calves at 0-3, 4-15, 16-30, 31-90, 91-180 and 181-365 days were 96.17±0.80, 86.17±2.12, 89.23±2.03, 80.39±2.89, 83.41±3.02 and 95.61±1.79 per cent, respectively. The significant (P